Reduced equations of slope-deflection method in structural analysis - Husain, Muhammed Abbas; Hasan, Zahraa Hameed (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an update of the slope-deflection method, which is used in the analysis of statically indeterminate structures. In this study, new reduced equations are presented based on including both the effects of the member rotations and the fixed end moments in one term, rather than two terms, in order to simplify the application of the slope-deflection method.
Keywords: indeterminate structures; slope-deflection; structural analysis; classical methods; reduced equations